2024
DOI: 10.1161/cir.0000000000001209
|View full text |Cite|
|
Sign up to set email alerts
|

2024 Heart Disease and Stroke Statistics: A Report of US and Global Data From the American Heart Association

Seth S. Martin,
Aaron W. Aday,
Zaid I. Almarzooq
et al.

Abstract: BACKGROUND: The American Heart Association (AHA), in conjunction with the National Institutes of Health, annually reports the most up-to-date statistics related to heart disease, stroke, and cardiovascular risk factors, including core health behaviors (smoking, physical activity, nutrition, sleep, and obesity) and health factors (cholesterol, blood pressure, glucose control, and metabolic syndrome) that contribute to cardiovascular health. The AHA Heart Disease and Stroke Statistical Update present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 446 publications
(79 citation statements)
references
References 3,734 publications
(3,892 reference statements)
1
21
0
Order By: Relevance
“…Older age is a known risk factor for stroke ( 1 ). Stroke prevalence among adults aged ≥65 years was consistent across the study period; however, prevalence among adults aged <65 years increased by approximately 15%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Older age is a known risk factor for stroke ( 1 ). Stroke prevalence among adults aged ≥65 years was consistent across the study period; however, prevalence among adults aged <65 years increased by approximately 15%.…”
Section: Discussionmentioning
confidence: 99%
“…Stroke is a leading cause of morbidity in the United States and was the fifth leading cause of death in 2021. * The estimated direct and indirect cost of stroke in the United States was $56.2 billion during 2019–2020 ( 1 ). A report on stroke prevalence using Behavioral Risk Factor Surveillance System (BRFSS) data indicated that overall self-reported stroke prevalence among noninstitutionalized adults aged ≥18 years in all 50 states and the District of Columbia (DC) had a relative decrease of 3.7% during 2006–2010 ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among modifiable risk factors, the global leader for cardiovascular disease (eg, myocardial infarction, heart failure, atrial fibrillation), neurovascular disease (eg, stroke and cognitive decline), death, and disability-adjusted life years is hypertension. 21,22 Faraci and Scheer 23 review accumulating evidence about the impact of circadian mechanisms in relation to changes in daily rhythms in blood pressure (eg, the normal reduction in blood pressure that occurs at night, nocturnal hypertension, and so forth). They compare and contrast differences in blood pressure regulation between humans and the most common preclinical models that are naturally nocturnal.…”
Section: Compendium: Circadian Mechanisms In Cardio/ Cerebrovascular ...mentioning
confidence: 99%
“…Acute myocardial infarction (MI), defined pathologically as myocardial cell death due to prolonged ischemia, is one of the leading causes of morbidity and mortality globally. The prevalence of the disease approaches 3 million people worldwide, with 605,000 new MIs diagnosed annually in the US [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Acute myocardial infarction (MI), defined pathologically as myocardial cell death due to prolonged ischemia, is one of the leading causes of morbidity and mortality globally. The prevalence of the disease approaches 3 million people worldwide, with 605,000 new MIs diagnosed annually in the US [1–3]. Echocardiography is a rapid, noninvasive, portable, and inexpensive imaging modality, making it the preferred technique for the assessment of MI patients [4, 5].…”
Section: Introductionmentioning
confidence: 99%